2013
DOI: 10.1007/s10608-013-9547-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Fear of Negative Evaluation and Eating Pathology During Intervention and 12-Month Follow-up

Abstract: Fear of negative evaluation, a core feature of social anxiety disorder, has been prospectively related to eating pathology over and above other established risk factors, suggesting that it may be an important cognitive risk factor for eating disorders. The present study examined reciprocal longitudinal relations among fear of negative evaluation and eating disorder risk factors using a female undergraduate sample (N=82) enrolled in an eating disorder prevention program. Cross-lagged panel analysis revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 77 publications
(109 reference statements)
4
20
0
Order By: Relevance
“…Two studies found that fear of negative evaluation predicted increased bulimic symptoms over time (Gilbert & Meyers, 2005; Hamann, Wonderlich-Tierney, & Vander Wal, 2009). Another study found that fear of negative evaluation increased body dissatisfaction and eating disorder symptoms (Deboer et al, 2013). Regarding perfectionism, one study found that general perfectionism predicted young adult onset of AN, but not BN (Tyrka, Waldron, Graber, & Brooks-Gunn 2002).…”
Section: Prospective Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies found that fear of negative evaluation predicted increased bulimic symptoms over time (Gilbert & Meyers, 2005; Hamann, Wonderlich-Tierney, & Vander Wal, 2009). Another study found that fear of negative evaluation increased body dissatisfaction and eating disorder symptoms (Deboer et al, 2013). Regarding perfectionism, one study found that general perfectionism predicted young adult onset of AN, but not BN (Tyrka, Waldron, Graber, & Brooks-Gunn 2002).…”
Section: Prospective Findingsmentioning
confidence: 99%
“…Several underlying vulnerabilities have been proposed to contribute to both social anxiety and eating disorders, and those that have received the most attention to date are perfectionism (e.g., Shafran, Cooper, & Fairburn, 2002), fear of negative evaluation (e.g., Deboer et al, 2013), and social appearance anxiety (e.g., Levinson et al, 2013). We will briefly outline each of the proposed vulnerability factors below and the existing research that has tested these factors in a combined model of shared vulnerability (Levinson & Rodebaugh, 2012; Levinson et al, 2013; Levinson & Rodebaugh, 2015).…”
mentioning
confidence: 99%
“…Results are corrected for multiple comparisons using a 5% false discovery rate (Deboer et al, 2013). Likewise, using the combined gene-positive group, associations between cortical thickness and accuracy measures from both tasks were examined using a general linear model and the FreeSurfer 'Different Onset, Same Slope' model (Fischl, & Dale, 2000;Fischl et al, 2002;Fischl et al, 2004).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Importantly, Deboer and Smits (in press) contribute a longitudinal study to this special issue to evaluate whether fear of negative evaluation (FNE) is a prospective risk factor for changes in thin ideal internalization, body dissatisfaction, restraint, disordered eating, and negative affect. Although this study did not include perfectionism, the examination of FNE closely aligns with Menatti et al’s (in press) examination of fear of public scrutiny in relation to bulimic symptoms.…”
Section: Commentary On Empirical Examinations Of the Association Betwmentioning
confidence: 99%